2022
DOI: 10.1016/j.jclinepi.2020.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Controversy and Debate: Questionable utility of the relative risk in clinical research: Paper 1: A call for change to practice

Abstract: Background and Objectives: In clinical trials, the relative risk or risk ratio (RR) is a mainstay of reporting of the effect magnitude for an intervention. The RR is the ratio of the probability of an outcome in an intervention group to its probability in a control group. Thus, the RR provides a measure of change in the likelihood of an event linked to a given intervention. This measure has been widely used because it is today considered a measure with ''portability'' across varying outcome prevalence, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 33 publications
0
102
0
Order By: Relevance
“…The effect measurement estimate of mortality risk chosen was the odds ratio (ORs) in our study. Risk ratio and hazard ratio in other studies were considered to be OR, as OR was shown to be a more effective measure 28 . If not available, the ORs were calculated by events and total numbers of patients in two groups.…”
Section: Methodsmentioning
confidence: 99%
“…The effect measurement estimate of mortality risk chosen was the odds ratio (ORs) in our study. Risk ratio and hazard ratio in other studies were considered to be OR, as OR was shown to be a more effective measure 28 . If not available, the ORs were calculated by events and total numbers of patients in two groups.…”
Section: Methodsmentioning
confidence: 99%
“…An intense debate is ongoing, with some considering the non-collapsibility of ORs and HRs to be an advantage for statistical modeling because the mathematical features that render a parameter non-collapsible also provide the properties that facilitate statistical analyses on the estimation scale, including the unlimited range of odds and hazard rates and the fact that they are non-linear functions of probabilities [ 9 , 22 ]. Others, however, argue that collapsible measures such as risk difference and mean survival time difference are preferable parameters to use because, in addition to being difficult to interpret clinically, the non-collapsibility of ORs and HRs adds to problems of transportability and makes it harder to compare estimates across studies [ 17 , 23 ].…”
Section: Statistical Estimationmentioning
confidence: 99%
“…For effect measures on a multiplicative scale (such as risk ratio, hazard ratio, or odds ratio) as opposed to the additive scale (such as risk differences), the analyses should be performed using the log-transformation and with the corresponding standard errors [3]. Importantly, effect modification may be present on one scale but not on another, and conflicting opinions exist on which scale to use [6]. The European Medicines Agency (EMA) recommends using the scale on which the endpoint is commonly analyzed, and to present supplementary analyses on the complementary scale where inconsistency is observed [7].…”
Section: Se Dmentioning
confidence: 99%